Design of Automatic Power Factor Correction for Optimization of Electric Energy Consumption - Restu Mukti Utomo; Adi Pandu Wirawan; Wisnu Candra Margono; Nur Rani Alham (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2024)
Electrical energy is a major human need which, when viewed from its main source, namely fossil energy, will increasingly run out. There needs to be an effort to utilize electrical energy more optimally. The problem discussed in this research is the decline in power factor. The State Electricity Company (PLN) has a minimum power factor standard of above 0.85 which is found in the SPLN 70-1 regulation and PERMEN ESDM No. 09 of 2011. If the power factor is below the minimum limit, it will result in losses, because consumers have to pay for excess kilo Volt Ampere Reactive hours (kVARh). Power factor drops are caused by the use of inductive loads. With automatic power factor correction, the poor power factor from the use of inductive loads will be resolved and optimization of the use of electrical energy can be achieved. From the test results conducted using 3 cumulative loads, the worst power factor value was obtained before PF repair was carried out by the system, namely 0.38 and after PF repair by the best power factor system reached 0.99 and obtained the value of active power and apparent power after PF repair is almost the same (comparable) and it can be said that the optimization of electrical energy occurs in this study.